(untitled) (Journal of Enam Medical College, 2024)
Background: Now-a-days determination of estrogen receptor (ER), progesterone receptor (PR) and HER-2/neu expression pattern by immunohistochemistry in invasive breast cancer have become the standard procedure for breast cancer management. Objective: To see the expression pattern of estrogen receptor, progesterone receptor and HER-2/neu in Bangladeshi women with invasive breast carcinoma. Materials and Methods: This retrospective study was performed in 67 cases of invasive breast cancer. Estrogen receptor (ER), progesterone receptor (PR) and HER-2/ neu expression pattern were assessed by immunohistochemistry using monoclonal antibodies for detecting estrogen and progesterone receptors, and polyclonal antibody for detecting HER-2/neu. Results: All the cases were graded according to Nottingham Modification of Bloom- Richardson system. Of those, Grade I tumours were 14 (20.89%), Grade II tumors were 45 (67.16%) and Grade III tumors were 8 (11.95%). Both ER and PR positive reactivity were the same and it was found 50 (74.63%) and HER-2/neu reactivity patterns were found negative in 45 (67.16%) cases and positive in 22 (32.84%) cases. Conclusion: ER, PR and HER-2/neu expression do not correlate with each other, so it is recommended that each test should be independently determined by immunohistochemistry in all cases of invasive breast cancer. All equivocal cases of HER-2/neu (score 2+) should be analysed by FISH technique to find out the percentage of real score. J Enam Med Col 2021; 11(3): 185−189